Pengembangan Bisnis Produk Manisan Pala Di Umkm My Sari Pala Dengan Pendekatan Metode Business Model Canvas - Azi Permana; Amar Ma'ruf; Delfitriani Delfitriani (JURNAL AGROINDUSTRI HALAL, 2024)
The word business is often encountered by the general public and is often understood as an activity that one does to earn money and livelihood. Most people aspire to own their own business, and it is very satisfying to have a profitable business that consistently makes money every month. Every entrepreneur is responsible for business development, which requires insight, drive and originality. If every entrepreneur can successfully do this, there will be a great opportunity for small businesses to grow into medium or even large businesses. A company called My Sari Pala is engaged in the food and beverage sector. My Sari Pala makes nutmeg-based foods, which are available in six types: candied nutmeg, nutmeg drinks, nutmeg syrup, candied nutmeg, nutmeg tea, and nutmeg cookies. One of the most popular enterprise development techniques is the enterprise Model Canvas. Nine blocks of topics related to the company's activities form a business model known as the company's Model Canvas. Customer groups, value propositions, channels, customer connections, revenue streams, critical resources, critical activities, critical alliances, and cost structures form the nine building blocks. Comparing the strengths, weaknesses, opportunities, and threats of a system is known as SWOT analysis. The internal and external strategic factors are put into a matrix known as the internal strategic factor matrix and internal strategic factor analysis summary. The external strategic factor matrix is also known as the External Strategic Factor Analysis Summary (EFAS).